Condition Monitoring System and Automatic Air Cleaning in the Toilet of Firebase-Based Andalas University Lecture Building - Multri Okta Ilham, Randa; Hadelina, Rizka; Hersyah, Mohammad Hafiz; Arief, Lathifah (CHIPSET, 2025)
Maintaining the cleanliness and comfort of toilets in lecture buildings is very important for the quality of the campus environment. This study develops a Firebase-based Automatic Air Condition Monitoring and Cleaning System in the restrooms of Andalas University lecture halls. The main problem identified is the lack of direct monitoring, which leads to the appearance of unpleasant odors and potential health problems. A survey showed that 64.8% of respondents sometimes felt unpleasant odors, while 59.3% indicated a lack of adequate air circulation.To solve this problem, the designed system is able to detect and monitor toilet conditions in real-time through gas measurements such as ammonia, hydrogen sulfide, and carbon monoxide using MQ-135, MQ-136, and MQ-7 sensors, the results of which can be monitored through a website. The system not only monitors, but also controls air quality by turning on the exhaust fan when the gas level exceeds a certain. Tests show that the system is accurate in detecting gas, with sensor precision above 90% and an average data transmission time of 1.74 seconds. However, the humidity measurement showed an error rate of 32.36%. The system effectively improves the hygiene monitoring of restrooms, thereby improving comfort and health on campus